THE MAKING PROCESS AND ORGANOLEPTIC TEST OF GREEN SPINACH FLAVOR WET NOODLES - Unusa, Sri Oyin; Modjo, Ardiyanto Saleh; Antuli, Zainudin (Universitas Negeri Gorontalo, 2023)
A study was conducted to understand the process of making green spinach noodles at K.U.B SRI REZEKI. Experimentation was the method employed in this activity. The preparation of raw materials is the initial stage in producing flavorful green spinach noodles, followed by sorting, washing, grinding, sifting flour, blending ingredients, milling, and finally, packaging. Results from organoleptic tests indicated that in taste evaluation, the panelists favored the 30:5 ratio in green spinach noodles. For color assessment, the highest average score was achieved at the 30:3 ratio, and in texture evaluation, the highest average score was also found at the 30:3 ratio. This differs from the other two ratios, namely 30:5 and 30:2.Keywords: Wet noodles, flavor, green spinach.